The Reception of Thucydides in the Theory and Practice of Hellenistic Historiography - Kurpios, Marcin (2021)
The book explores the significance of that work for the generations of historians and other authors in the Hellenistic age (323-31 BC). It is the first monograph that fully treats the question of the fate of the History in the Hellenistic world. The book collects and analyses for the first time all the fragmentary evidence on Thucydides' readership from the Classical and the Hellenistic period. It includes a thorough and up-to-date synoptic introduction and extensive bibliography, setting each chapter in the context of broader scholarship from XIXth century onwards.. With this book, readers shall receive a survey of manifold aspects of Thucydides in particular, and of historical writing in the Hellenistic age in general.